The Higher Education Curriculum in the Era of Industrial Revolution 4.0: A Review on Economic Education at the State University in Malang and Surabaya - Benita, Almas Zerlina; Surjanti, Jun (International Journal of Research and Community Empowerment, 2025)
The Industrial Revolution 4.0 demands that higher education institutions adapt their curricula to produce graduates with essential skills in data literacy, technological literacy, and human literacy. This study aims to analyze the curriculum adjustments made by State University in Malang and Surabaya in the field of Economic Education. Using a literature review methodology, the study draws upon national and international journal articles to examine the design, implementation, and evaluation of the Economic Education curricula at both universities. The findings indicate that both institutions have successfully integrated innovative teaching methods and aligned their curricula with the principles of the Merdeka Belajar Kampus Merdeka (MBKM) initiative. This curriculum adaptation ensures that graduates are equipped with the necessary competencies to navigate and succeed in a rapidly evolving global economy. The research provides insight into the ongoing curriculum reform efforts and offers recommendations for future studies to evaluate the long-term impact of these changes on graduate employability and industry relevance.